Dermal exposure and surface contamination associated with the use of a cobalt-chrome alloy during additive manufacturing - Paulse, Lynicka; du Preez, Sonette; Franken, Anja; du Plessis, Johan (Annals of work exposures and health, 2025)
Amidst the rapidly emerging additive manufacturing (AM) industry, not enough attention has been given to dermal exposure, with only one previous study that assessed dermal exposure to metals. Our study aimed to characterise a cobalt (Co)-chrome (Cr) alloy feedstock powder (CO-538) in terms of particle size, shape, and elemental composition, and assess dermal exposure and workplace surface contamination during powder bed fusion AM. Particle size distribution (PSD) and shape of the virgin and used feedstock powder were determined using static image and scanning electron microscopy analyses. The elemental composition of powders was established using inductively coupled plasma-optical emission spectrometry. A removal wipe sampling method using Ghostwipes was performed on AM operators' skin at various locations (index finger, palm, wrist, back of the hand, and neck), before and after each AM processing phase. Workplace surfaces (both AM and non-AM areas) were also sampled before and after each shift using a removal wipe method to measure surface contamination. PSD analysis revealed a significant difference (P ≤ 0.05) in median size, with used powder exhibiting smaller particles than virgin, where 10% of particles were smaller than the given diameter. Additionally, significant differences (P ≤ 0.05) were noted in the mean circularity and convexity between virgin and used powders, indicating that used powder particles were more irregular and rougher compared to virgin. The CO-538 feedstock powder contained Co, Cr, molybdenum (Mo), aluminium (Al), iron (Fe), and Ni. These metals were also detected on the skin of AM operators and on surfaces within the AM and non-AM areas of the facility. Dermal exposure occurred on all of the anatomical areas, with the highest total metal concentration detected on the index finger during the post-processing phase of AM. The highest full-shift geometric mean GM concentration of each metal was detected on the finger and followed a trend of Co > Cr > Fe > Al > Mo > Ni. Surface contamination occurred on all AM and non-AM sampling areas after a full shift. Dermal exposure to all CO-538 alloy metal constituents occurred on all sampled anatomical areas during all three processing phases. Measurable concentrations of metals that were detected on all sampled surfaces indicate that cross-contamination between AM and non-AM areas occurs and that these surfaces may act as a secondary source of exposure. There is thus a need for control measures to be implemented in AM facilities to eliminate or reduce surface metal contamination and dermal exposure.